TFR2 p.A75V mutation aggravates liver iron overload in alcoholic liver disease via ERK pathway - Chao Xie; Yingying Liu; Xiaofan Wang; Long Huang; Xiaoming Wang; Wei Zhang; Lina Wu; Tianhui Liu; Ping Wang; Lin Liu; Xu Fan; Jidong Jia; et al. (Journal of Molecular Medicine, 2026)

A data-driven framework for effective single-group cross section adjustment in point-depletion burnup calculations - Wei-Jia Meng; Te Sheng; Ou-Yi Li; Gang-Lin Yu (Annals of Nuclear Energy, 2026)

Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

Dynamic response analysis of submerged floating tunnels under multi-hazard effects part II: Wave-current interaction - Weijun Zhang; Yan Jin; Dongsheng Qiao; Lin Lu; Zhiwen Yang; Guoqiang Tang; Jinping Ou (Ocean Engineering, 2026)

Physics-environment augmented Attention-LSTM approach for mooring tension prediction - Jin Hu; Dongsheng Qiao; Pengfei Liu; Guoguang Sun; Ziming Wang; Guoqiang Tang; Yunfei Teng; Lin Lu; Jinping Ou (Ocean Engineering, 2026)

Asymmetric coordination configuration unlocks single-atom nanozyme catalytic activity for redox-immune homeostasis and temporomandibular joint osteoarthritis therapy via macrophage depolarization and cGAS-STING pathway inhibition - Kaixun He; Hanyu Lin; Penghui Wei; Hongjia Zheng; Zhonghan Chen; Sihui Zhang; Yanjing Ou; Wenting Jiang; Wenxiu Yuan; Geyuan Zheng; Jiang Chen; Yi Zuo; et al. (Chemical Engineering Journal, 2026)

Retraction notice to ‘Association between prenatal exposure to ambient particulate matter and risk of hypospadias in offspring: A systematic review and meta-analysis’ [Environ. Res. 192 (2021) 110190] - Hua-Chuan Lin; Jing-Min Guo; Pin Ge; Ping Ou (Environmental Research, 2026)

Settlements sculpted by water: Revealing the shaping power of water networks on urban morphology in China - Lin Fang; Ke Song; Qiong Liu; Minghao Ou (Environmental Impact Assessment Review, 2026)

Weather source heterogeneity affects disease forecasting: A case study of rice bacterial leaf blight in Taiwan - Jie-Hao Ou; Guo-Cih Lin; Yea-Fang Wu; Chi-Yu Chen; Guan-Ying Huang; Hau-Ping Chou; Chien-Chih Kuo; Hsin-Yuh Wu; Qiao-Juan Lai; Chih-Wei Wang; Yi-Chen Tsai; Chang-Hsin Kuo; et al. (Agricultural and Forest Meteorology, 2026)

Phylogeny and taxonomic revisions of Piper (Piperaceae) in Taiwan - Po-Hao Chen; Chia-Hao Chang; Kuan-Ning Kung; Hung‑Chih Lin; An-Ching Chung; Chia-Ying Ou; Shih-Hui Liu (Journal of Plant Research, 2026)
Taiwan, located at the northernmost extent of Huxley’s Line, marks the furthest point along this biogeographic boundary where exchanges of flora and fauna occur. The genus Piper , a globally distributed and taxonomically complex group of both economic and evolutionary importance, has a convoluted taxonomic history in this transitional zone that requires comprehensive study. Here, we integrate morphological, molecular, and distributional data to revise the taxonomy of Taiwanese Piper , resolve their evolutionary relationships, and infer their biogeographic history. Our revision recognizes 11 species in Taiwan, including seven native taxa, of which three are endemic. The present analysis establishes the first comprehensive phylogenetic framework for Taiwanese Piper and reveals that native species arose from lineages on both sides of Wallace’s Line. Collectively, these findings provide the first evidence of bidirectional expansion within a genus in Taiwan and position Piper as an exemplary system for examining phylogeographic dynamics in transitional biogeographic zones.

Semaglutide treatment reverses HFD induced hippocampal microglia activation and improves cognitive dysfunction - Haodong Gong; Junlu Liu; Yihan Wang; Xufan Lin; Guangsen Wu; Yichao Ou; Mingfeng Zhou; le Yang; Junxiang Peng; Xinyun Ye; Yongjia Wang; Fei Xu; et al. (Tissue and Cell, 2026)

Baicalin alleviates repeated superovulation induced ovarian dysfunction and oocyte impairment by suppressing excessive glycolysis - Lin-Feng Li; Hao Shen; Zhi-Min Qi; Tian Luo; Sheng-Ming Liu; Li-Li Ou; Chang-Long Xu; Yu Liu (Theriogenology, 2026)

Nonlinear coupled dynamic response of TLP wind turbine with redundant mooring under complex environmental loads and multi-tendon failures - Mingyang Wei; Jianhua Zhang; Ke Sun; Yian Chen; Zaibin Lin; Yan Geng; Hongwen Liu; Yanghua Ou (Ocean Engineering, 2026)

Seasonal variation of fish biodiversity in Xisha Islands based on dual-marker eDNA metabarcoding - Shengming Deng; Yuguo Ye; Min Liu; Bai-an Lin; Chengdan Ma; Yifeng Xu; Yongcan Zhou; Shifeng Wang; Weiliang Guo; Huilong Ou; Xiang Zhang; Jianlong Li (Marine Environmental Research, 2026)

Universal primer-based RPA combined with parallel CRISPR/Cas12a decoding for rapid multi-species meat authentication - Shuang Han; Xinyi Lin; Yuting Lei; Zhen Liu; Jiayang Li; Xueling Ou (Food Chemistry, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

Cover crop mixtures composed of three functional groups enhanced ecosystem multifunctionality in a subtropical citrus orchard - Xinyu Zou; Hailin Zhang; Jiaxin Ren; Huiping Ou; Lin Yang; Xiaojun Shi; Jie Wang (Plant and Soil, 2026)
Aims Cover crops enhance agroecosystem multifunctionality by modulating biodiversity, yet knowledge of their functional diversity remains limited. This study aimed to systematically evaluate the effects of cover crop species richness (SR) and functional group richness (FGR) on ecosystem multifunctionality (EMF) in citrus orchards. Methods This study assessed 33 cover crop planting schemes in citrus orchards in Southwest China, using six species arranged in gradients of SR (1, 2, 3, 4, 6) and FGR (1, 2, 3). Seasonal variations in soil properties, cover crop yield, and weed biomass were measured. Individual ecosystem functions and EMF across SR and FGR gradients were evaluated. The Random Forest Model and Structural Equation Modeling identified key drivers and mechanisms of EMF. Results (1) Cover crop polycultures suppressed weeds, increasing seasonal cover crop yield by 10–30% compared to single-species cover crops. They reduced soil temperature in spring, summer, and autumn while increasing it in winter. (2) SR and FGR exhibited quadratic correlations with EMF. FGR had a stronger influence, maximizing EMF (Mmde = 13.66) at a lower threshold (Tmde = 77%), compared to SR (Mmde = 12.86, Tmde = 84%). (3) Key EMF predictors included cover crop yield, soil alkali-hydrolyzable nitrogen, weed biomass ( p < 0.01), and soil organic matter, temperature, urease activity (0.01 < p < 0.05). SR and FGR directly enhanced EMF via cover crop yield (0.51) and indirectly via reduced weeds biomass (-0.33). Yield and weed biomass further acted through soil properties (temperature: 0.06, organic matter: 0.09, alkali-hydrolyzable nitrogen: 0.26). Conclusions FGR manipulation outperforms SR for enhancing EMF, offering a sustainable citrus orchard management strategy.

LncRNA DLX6-AS1 Regulates the Pathological Process Related to Alzheimer’s Disease via miR-204-5p - Minggang Jiang; Yang Lin; Liping Wang; Kaiyun Ou (NeuroMolecular Medicine, 2026)

The sustained expansion (2011−2022) and abrupt contraction (2023) of the Ross Sea polynyas - Xiaolu Ou; Lingqiao Cheng; Dongming Lin; Guoping Zhu (Journal of Marine Systems, 2026)

A low-power and visualized varicose vein ablation surgery based on interventional optical fiber therapeutic probe - Fangzhou Jin; Yinsheng Lin; Yading Luo; Jian Han; Xu Yue; Wenwei Chen; Yongkang Zhang; Shanshan Guo; Xiaobing Niu; Jun Guo; Bai-Ou Guan; Chengzhi Li; et al. (Chemical Engineering Journal, 2026)

Weak GPS signal tracking using block coherent integration based on NN discriminator - Zhiqiang Gong; Honglei Lin; Zhe Liu; Gang Ou (GPS Solutions, 2026)

Habitats guarded by terrain: The beneficial role of topographic heterogeneity in securing habitat quality - Lin Fang; Yujun Wang; Qiong Liu; Yanxiao Liu; Minghao Ou (Applied Geography, 2026)

Moderate net-chasing enhances stress resilience in freshwater prawns Macrobrachium rosenbergii: evidence from behavioral and physiological recovery - Jiangtao Li; Jiale Zhou; Licheng Zeng; Yingtong Ou; Zhongjie You; Zheng Xiao; Jianjun Guo; Li Lin; Xiaojing Lv (Aquaculture, 2026)

Mechanistic responses of coccolithophores to exposure to the marine pollutant atrazine - Xiang-Wu Chen; Yi-Tong Huang; Yue-Tao Song; Zhuo-Fan Li; Xue-Ling Huang; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Avermectin disrupts blood-brain barrier integrity in zebrafish larvae via the Wnt/β-catenin signaling pathway - Wei-Guo Wang; Lin-Jing Du; Huan-Ou Ma; Wen-Ping Xu; Li-Ming Tao; Zhong Li; Jia-Gao Cheng; Li Zhao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Association between lipid oxidation, water activity and aflatoxin B1 risk reversal in stored sunflower seeds: A storage microenvironment observation study - Sen Zeng; Jiamin Song; Xuan Ou; Tinyan Sang; Siying Lin; Ruixia Zhang; Jie Chen; Yuhua Tang; Songlei Wang; Yanan Sun (Journal of Stored Products Research, 2026)

Application of a novel complex surfactant to enhance the bioremediation of weathered-diesel oil contaminated soils: mechanism and mesocosm-scale study - Wei-Ting Chen; Jiun-Hau Ou; Wei-Zhe Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Soils and Sediments, 2026)

Tracing the evolution of granitic magmas revealed by fayalite–ferrosilite-bearing microgranular enclaves in Jiuyishan area of South China Block - Jing-Yi Liu; Quan Ou; Jian-Qing Lai; Feng Zi; Kun Wang; Wen-Zhou Xiao; Zhi-Cheng Lin; Cui-Yun Wang; Qian-Cheng Feng; Jia Liao (Acta Geochimica, 2026)

Deep eutectic solvent-based ultrasound extraction of bioactive flavonoids from Coreopsis tinctoria Nutt.: Process optimization, HPLC analysis, and preliminary bioactivity evaluation - Peng Wen-Yu; Lin Fang-Qi; Mo Hong-Bo; Hu Tong-Yi; Ou Hong (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Online probabilistic forecast of landslide failure time via multi-information fusion - Mingxi Chen; Penghui Lin; Jie Jiang; Xiaoduo Ou; Qinghui Jiang; Xiaojie Tan (Engineering Geology, 2026)

Experimental Study on Shear Anisotropy and Anchoring Mechanism of Fractured Rock Masses - Shuguang Zhang; Jiamian Lin; Wenbo Liu; Xiang Huang; Dipeng Zhu; Wenwu Ou; Shutian Zhao; Yipin Liu; Yingbo Li (Geotechnical and Geological Engineering, 2026)

Comparative study on the generation and migration characteristics of blasting dust and toxic gases in high-altitude tunnel: based on field measurements and CFD - Minglei Lin; Jianguo Liu; Mulati Jueraiti; Wen Nie; Linquan Tong; Jie Yu; Tianyue Wang; Shengnan Ou; Longzhe Jin (Tunnelling and Underground Space Technology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A stable environmental niche for humans in the southern Levant 70–40 ka - Mahmoud Abbas; Zhongping Lai; Hua Tu; Xianjiao Ou; Paul A. Carling; Penghui Lin; Mohammad Alqudah; Bety S. Al-Saqarat; Ting Qiu; Michael D. Petraglia; Zeljko Rezek; John D. Jansen (Quaternary Science Reviews, 2026)

End-to-end intelligent rapid design method for bridge single-pile based on generative adversarial networks - Buyu Jia; Zhaofan Liang; Wentao Ou; Yujun Lin; Xiaolin Yu (Engineering Structures, 2026)

Extracellular vesicles in pregnancy-related disorders: from mechanisms to clinical implications - Xiaojing He; Shiqi Liu; Yudi Wang; Hualongyue Du; Qiaoxi Lin; Wenhui Wang; Zihao Ou; Lei Zheng (Science China Life Sciences, 2026)

Construction of a coccolithophore database platform for ecological and molecular applications - Xue-Ling Huang; Yi-Xin Xiong; Shuang Yu; Xiang-Wu Chen; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Engineered bacterial extracellular vesicles drive anti-tumor immunity via dendritic cell maturation and trafficking - Zihao Ou; Qianbei Li; Bonan Pan; Junjie Feng; Xiaojing He; Yuanyuan Wu; Yudi Wang; Zhen Cai; Jinduan Lin; Lei Zheng (Chemical Engineering Journal, 2026)

Effects of forest-medicinal plant intercropping on soil carbon pools in coastal saline-alkali land - Kaiwen Huang; Jinling Wang; Jie Kuai; Xin Liu; Jiajun Ou; Jiayi Miao; Ke Huang; Jie Lin (Plant and Soil, 2026)

Phylogeographic Pattern and Genetic Structure of the Cyprinid Fish Microphysogobio kachekensis (Oshima 1926) in Mainland China and Hainan Island Based on Mitochondrial and Nuclear DNA - Jin-Quan Yang; Jiabo Chen; Junjie Wang; Tian-Qi Zhou; Yuh-Wen Chiu; Hung-Du Lin; Wen-Sheng Ou (Fishes, 2026)
South China’s freshwater biodiversity has been shaped by Quaternary climatic oscillations and persistent geological barriers. We investigated the phylogeography and conservation implications of the primary freshwater fish Microphysogobio kachekensis across mainland China and Hainan Island using mitochondrial (cyt b and control region) and nuclear (RAG2 and rpS7-1) markers from 200 individuals. Mitochondrial analyses recovered two major lineages and multiple sublineages largely structured by drainage basins, whereas nuclear data resolved four geographically concordant lineages. Population differentiation was strong (high FST), and SAMOVA/AMOVA supported major barriers restricting gene flow, including the Qiongzhou Strait, Gulf of Tonkin, Yunkai Mountains, and Nanling Mountains. Ancestral-area reconstruction inferred the Pearl River region as the most likely source area, followed by dispersal to northern Hainan and subsequent expansion to southern Hainan and the Red River, with additional northward expansion to the Zhejiang–Fujian region. Despite high haplotype diversity, within-population nucleotide diversity was low, consistent with long-term river isolation and complex demographic history. We propose six ESUs and four MUs for evolutionarily informed conservation and to guide stock enhancement in southern China.

Data augmentation-based evidential generative adversarial network for open-set hyperspectral image classification - Lin Song; Longpo Yang; Keren Shi; Yuan Ou; Zongfang Ma (International Journal of Remote Sensing, 2026)

Integrated transcriptomic and metabolomic analyses reveal the molecular adaptive mechanisms of Schizopygopsis chengi baoxingensis under acute heat stress - Hangyu Lin; Xiaoyun Wu; Ya Liu; Jun Ou; Luyun Ni; Feiyang Li; Jiansheng Lai; Quan Gong; Jue Lin; MingJiang Song (Journal of Thermal Biology, 2026)

Thermodynamic and economic analyses of a biomass gasification-based ammonia and electricity polygeneration system integrating semi-closed supercritical CO2 cycle and chemical looping air separation - Siyi Ou; Xin Chen; Lin Zhu; Yu Liu; Qiang Hao; Rou Zheng; Yucen Chen; Jie Li (Fuel, 2026)

Mechanism and dynamic evolution of LED irradiation on volatile metabolites: A novel strategy for optimizing aroma quality in innovative black tea - Jihang He; Xinru Yu; Yunzhi Hao; Qiuming Li; Qingyang Wu; Xiaoxi Ou; Ying Xu; Hongzheng Lin; Ziwei Zhou; Yun Sun (Food Chemistry, 2026)

Modified p-y curves for wind turbine monopiles incorporating small-strain stiffness in sand - Yuqi Jiao; Dongsheng Qiao; Yongjie Tan; Guoqiang Tang; Lin Lu; Jinping Ou (Computers and Geotechnics, 2026)

Highly stretchable and self-adhesive PEDOT:PSS blends via coulombic repulsion-induced weakening of interchain interaction - Xiaoxue Lin; Rui Chen; Zeping Ou; Wen Sun; Lei Wang; Zhihan Zeng; Hanlin Cheng; Kuan Sun; Jianyong Ouyang (Chemical Engineering Journal, 2026)

Single-Cell eQTL Revealing Brain Cell-Type-Specific Genetic Control of Insomnia - Chengying Ou; Qiongxi Lin; Xiaoyun Hu (Journal of Molecular Neuroscience, 2026)

Coupled polyphosphate storage and DOP mobilization along estuarine gradients in the Pearl River Estuary - Xian-Yang Zhang; Feng-Xian Han; Jian-Ting Li; Jia-Xue Wu; Song-Hui Lu; Lin-Jian Ou (Marine Pollution Bulletin, 2026)

FINDER: Flow-aware intelligent navigation through distilled experience and reinforcement learning for UUVs in complex flow fields - Shuguang Chu; Haihan Feng; Yuheng Ou; Mingwei Lin; Dejun Li (Ocean Engineering, 2026)

Growth phase-linked Sargassum-associated DOM structures microbial succession and carbon-nutrient coupling in a benthic Sargassum bed - Xiao-Li Ou; Long-Long Huang; Qiu-Jie Wang; Li-Li Xu; Lin-Jian Ou; Yu-Feng Yang (Marine Environmental Research, 2026)

Biofilm-mediated mitigation of nitrous oxide emissions in anammox-based wastewater treatment - Zhiman Lin; Jinfan Zhang; Ru Wang; Jingmin Ou; He Zhang; Zihua Wang; Fangyuan Zheng; Xiantao Sun; Xin Wei; Yiming Huang; Zhenguo Chen; Mark C.M. van Loosdrecht; et al. (International Biodeterioration & Biodegradation, 2026)

Exacerbating or mitigating landscape fragmentation: Exploring the role of topographic heterogeneity in shaping landscape patterns in China - Lin Fang; Lei Yang; Qiong Liu; Minghao Ou (Environmental Impact Assessment Review, 2026)

Dl‑3‑n‑Butylphthalide Protects the Blood–Brain Barrier in Neonatal Hypoxic‑Ischemic Brain Damage by Alleviating Endothelial Cell Ferroptosis via the SLC7A11/GSH/GPX4 Pathway - Jiahao Ou; Qianqian Yu; Yuqi Luo; Ming Shen; Jia Lou; Saizhi Jiang; BangMing ye; LiZi Lin; Jianghu Zhu; Zhenlang Lin; Mingchu Fang (Molecular Neurobiology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Dynamic response analysis of submerged floating tunnels under multi-hazard effects part I: Theory and modeling - Weijun Zhang; Yan Jin; Dongsheng Qiao; Lin Lu; Guoqiang Tang; Jinping Ou (Ocean Engineering, 2025)

Regime shift in river-tide dynamics of longitudinal and transverse channels over the Pearl River Delta, China - Bo Li; Hao Yang; Huayang Cai; Suying Ou; Feng Liu; Tongtiegang Zhao; Kairong Lin; Jianliang Lin (Journal of Hydrology, 2025)

From human-driven eutrophication to effective management: Controlling brown tides in the coastal waters of Qinhuangdao, China - Lei Cui; Yue-Lei Dong; Jian-Le Zhang; Wei-Dong Yang; Song-Hui Lu; Lin-Jian Ou (Harmful Algae, 2025)

Preparation of fish oil microcapsules for enhanced stability and controlled release via plug-and-play microfluidic chips - Peilan Xie; Zhenqian Tang; Ba Guan; Yimeng Tang; Qiyou Chen; Jiaying Ou; Kangmin Lin; Zhuo Jiang (Food and Bioproducts Processing, 2025)

Effects and Mechanisms of NMDAR-EphB2 on Synapses in Mice by Active Immunization with a GluN1 Peptide - Kai Qian; Youshi Meng; Lin Zhang; Lanfeng Sun; Sijie Ou; Rida Li; Chi Gong; Shengyu Yang; Yuan Wu (Molecular Neurobiology, 2025)

Inhibitors of NADH–O-methylquinone compound a class of antitubercular drugs - Dongzi Lin; Cheng Xu; Changyou Gan; Bihua Ou; Fengxian Luo; Zhigang She; Lei Zhou; Zhenhua Chen (Molecular Diversity, 2025)

Fluoride removal from groundwater via powder-nano MgO adsorption: novel adsorbents development and mechanisms studies novel adsorbents development and mechanisms studies - Jiun-Hau Ou; Ssu-Ching Chen; Wei-Zhe Lin; Francis Verpoort; Rao Y. Surampalli; Chih-Ming Kao (Environmental Science and Pollution Research, 2025)

The distribution characteristics of marine litter in the intertidal zone of Lvhua Island and its impact on the macrobenthic community structure - Kaiyi Wang; Shuhan Wang; Jianing Sun; Qiao Zou; Jiaming Ou; Li Li; Shouyu Zhang; Xueping Lin; Kai Wang (Marine Environmental Research, 2025)

A photodynamic inactivation-mediated 5-aminolevulinic acid-grafted chitin film for preserving salmon: antibacterial efficiency and storage quality maintenance - Huajian Ou; Lu Chen; Qiaohui Zeng; Zhiyun Peng; Zihao Lin; Ping Qi; Konglong Feng; Jing Jing Wang (Food Chemistry, 2025)

Targeting cuproptosis by FDX1 in acetaminophen-induced liver injury - Yan Liu; Ying Yang; Baizhao Peng; Zhongyue Ou; Anna Zuo; Zihao Jiang; Chuanghai Wu; Hiu Yee Kwan; Ke Ma; Lin Yu; Xiaoshan Zhao (Chemico-Biological Interactions, 2025)

ML385 increases ferroptosis via inhibiting Nrf2/HO-1 pathway to enhances the sensitivity of MCF-7 TAMR to tamoxifen - Jie Yuan; Wenjun Huang; Minxia Lin; Shishen Sun; Fei Zhong; Lei Ye; Hao Yin; Xiaowei Ou; Zhiqiang Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Unraveling contributors to stepwise water level variations in the Zhujiang River Estuary - Bo Li; Hao Yang; Jing Liu; Feng Liu; Suying Ou; Jianliang Lin; Huayang Cai (Acta Oceanologica Sinica, 2025)

Heterojunction and electrolyte engineering of carbon-nanobow with built-in dual anions vacancies for sodium-metal storage - Jingjing Liu; Zili Yang; Quanzhi Lin; Feixue Luo; Mingjie Ou; Dan Tu; Wenyao Yang; Jianhua Xu; Yajie Yang (Chemical Engineering Journal, 2025)

Isolation, evolution, and biological characterization of non-virulent and non-drug-resistant Escherichia coli from porcine intestine - Bingming Ou; Biyang Xiao; Qingqing Li; Jiayi Wang; Xue Lin; Weinan Zhong; Huimin Zhu; Yufu Liu; Shaoting Li; Hongmei Zhang; Wenhua Liu; Minyu Zhang (Folia Microbiologica, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

A bioluminescent enzyme immunoassay based on nanobody-nanoluciferase fusion protein for the detection of fenpropathrin - Luo-Ji Yang; Lin Luo; Ai-Fen Ou; Hao-Sheng Zheng; Ya-Ru Li; Qileng Aori; Änatoly V. Zherdev; Zhen-Lin Xu (Food Bioscience, 2025)

Antimicrobial activity and preservation efficiency of TEMPO-oxidized chitin/5-aminolevulinic acid films mediated by photodynamic inactivation against salmon fillets - Huajian Ou; Lu Chen; Qiaohui Zeng; Wangsheng Qiu; Zihao Lin; Konglong Feng; Guang Liu; Ping Qi; Weijuan Huang; Jing Jing Wang (Food Packaging and Shelf Life, 2025)

Two-stage dynamic shear response of square RC columns under lateral impact: Mechanisms, inertial force analysis, and punching shear resistance model - Fei-Fan Feng; Lin Chen; Dai-Jiang Zhou; Tao Liu; Dao-Gang Ou; Yong Lu (Engineering Structures, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Phenological growth stages and the extended BBCH scale for djulis (Chenopodium formosanum Koidz.) - Shu-Chung Wu; Chih-Chung Lin; Chia-Ying Ou; Shih-Hui Liu (Journal of Plant Diseases and Protection, 2025)

Bclaf1 mediates super-enhancer-driven activation of POLR2A to enhance chromatin accessibility in nitrosamine-induced esophageal carcinogenesis - Xiangjun Zhou; Xueqiong Zhou; Jun Li; Yingzheng He; Shizhen Qiu; Ye Xu; Zeyu Liu; Yina Yao; Jia Liu; Ying Wen; Sitong Xie; Jialong Chen; et al. (Journal of Hazardous Materials, 2025)

Cotreatment strategy for hazardous arsenic-calcium residue and siderite tailings via arsenic fixation as scorodite - Rui Su; Xinrong Su; Yanjiao Gao; Xu Ma; Xiaoming Zhao; Xiaoxia Ou; Yubo Cui; Jinru Lin; Yuanming Pan; Shaofeng Wang (Journal of Environmental Sciences, 2025)

Three new sesquiterpenes with cytotoxic activity from Croton tiglium - Wen-Ying Zhou; Xiao-Xiao Zheng; Yang-Mei Ou; Yang-Lin Ou; Hong-Yu Jang; Yu-Xin Peng; Yi-Yi Wang; Bi-Qing Zhao; Li Li (Phytochemistry Letters, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

Comparing Cr(III) oxidation intermediated by different manganese oxidizing bacteria: Efficiencies, kinetic and key structure characteristics of biogenic manganese oxides - Guangyuan Tu; Chunyu Ou; Qi Liao; Xiaoming Zhang; Shuangle Hou; Lin Yu; Kun Li; Sen Yang; Qi Li; Weichun Yang; Qingzhu Li; Mengying Si; et al. (Environmental Research, 2025)

GLA deficiency causes cardiac hypertrophy via enhanced autophagy - Wei Ou; Xi Li; Kuo Tang; Lin Ding; Tingting Sun; Qian Li; Tao Li (Science China Life Sciences, 2025)

Use of non-targeted metabolomics to explore metabolic differences between stem cells and callus of Tetraena mongolica - Yeru Yang; Haihua Li; Ruiping Wang; Jiahe Li; Ling Li; Jiayu Li; Lin Ou; Jun Li; Chengbo Zhang; Liyu Wang; Fengqiang Yu; Zhi He; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

N6-methyladenosine-modified circ_0000517 promotes non-small cell lung cancer metastasis via miR-1233-3p/CDH6 axis - Weixian Lin; Lifang Huang; Zhu’an Ou; Yiwen Xuan; Daoqi Zhu; Qipeng Zhang; Enwu Xu (Journal of Molecular Histology, 2025)

Mechanical properties and failure modes of discontinuous jointed considering water softening effects - Siyu Chen; Hang Lin; Ke Ou; Xing Zhang; Chaoyi Yang (Earth Science Informatics, 2025)

Novel impact of metal ion-induced cell death on diabetic cardiomyopathy pathogenesis and therapy - Jingjing Jiang; Shengnan Hu; Kaibo Hu; Leyang Xiao; Jitao Lin; Yixuan Chen; Deju Zhang; Yangliu Ou; Jing Zhang; Linhui Yuan; Wenting Wang; Peng Yu (Apoptosis, 2025)

Stair-Stepping metamaterial and the derived isolator for all-DOF vibrations with multi-payloads - Haifeng Ou; Jia Zeng; Minqing Lin; Yifan Wang; Yujun Zeng; Xi Fang; Lingling Hu (Engineering Structures, 2025)

Effects of 2-hydroxypropyl-β-cyclodextrin and 28-homobrassinolide on the physiological characteristics, gene expression and terpenoid indole alkaloid accumulation in Catharanthus roseus cambial meristematic cell cultures - Fangfang Fu; Haihua Li; Li Ling; Jiahe Li; Yifei Chen; Weijie Hu; Jiayu Li; Lin Ou; Zhaoxi Chen; Jun Li; Pengfei Zhou (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Assessing Chinese user satisfaction with electric vehicle battery performance from online reviews - Lanxin Shi; Shiqi (Shawn) Ou; Yanzi Zhou; Yonglin Wu; Xiaolu Tan; Xin He; Daniel J. De Castro Gomez; Zhenhong Lin (Transportation Research Part D: Transport and Environment, 2025)

Linoleic acid alleviates aluminum toxicity by modulating fatty acid composition and redox homeostasis in wheat (Triticum aestivum) seedlings - Yiqun Ou; Zhuoran Teng; Yuchen Shu; Yi Wang; Dan Wang; Chengliang Sun; Xianyong Lin (Journal of Hazardous Materials, 2025)

FGF21 Alleviates Hypoxic-Ischemic White Matter Injury in Neonatal Mice by Mediating Inflammation and Oxidative Stress Through PPAR-γ Signaling Pathway - Mingchu Fang; Liying Lu; Jia Lou; Jiahao Ou; Qianqian Yu; Xiaoyue Tao; Jianghu Zhu; Zhenlang Lin (Molecular Neurobiology, 2025)

Late Mesozoic Wangxiang Composite Granitic Pluton, South China Block: Implications to Magma Emplacement and Evolution from Geochemical Proxies - Quan Ou; Jing-Yi Liu; Feng Zi; Bruna B. Carvalho; Xiaoping Long; Jian-Qing Lai; Kun Wang; Zi-Qi Jiang; Yi-Zhi Liu; Zheng-Lin Li; Hong-Yun Wang (Journal of Earth Science, 2025)

Rainfall Promote Bruceine D Release from Brucea javanica Leaf Litter Thus Reducing Weeds and Enhancing Plant Competitiveness - Yao Tong; Hai-Ou Lin; Dong-Qiang Zeng; Fa-Yang Xie; Wen-Wei Tang (Journal of Chemical Ecology, 2025)

Motor-Cognitive Dual-Task Cost and Associated Micro Lesions of Cerebellum and Brainstem in Multiple System Atrophy (Parkinsonian Type) - Yi Xiao; Shichan Wang; Yanbing Hou; Junyu Lin; Tianmi Yang; Qirui Jiang; Jiyong Liu; Ruwei Ou; Chunyu Li; Huifang Shang (The Cerebellum, 2025)

Can the Endophytic Microbial Compositions in Tomato Roots be Reshaped by Application with Wood Vinegar Under Continuous Cropping System - Jian Xiao; Junqian Feng; Qiang Lin; Hui-Ping Ou; Shangdong Yang (Journal of Soil Science and Plant Nutrition, 2025)

Erratum: wet bias of summer precipitation in the northwestern Tibetan Plateau in ERA5 is linked to overestimated lower-level southerly wind over the Plateau - Tinghai Ou; Deliang Chen; Jianping Tang; Changgui Lin; Xuejia Wang; Julia Kukulies; Hui-Wen Lai (Climate Dynamics, 2025)
We sincerely apologize for a technical error revealed in this article, published in 2023: the spectral nudging process at the upper levels was not functioning as intended. Consequently, the final results presented in the original work are based on WRF downscaling without active spectral nudging. To assess the potential impact of this error on the study’s main conclusion, we conducted two additional experiments using the same WRF version 3.7.1. Results show that the technical error does not alter the main conclusion of the study: the ERA5 overestimation of summer precipitation over the northwestern Tibetan Plateau is associated with an overestimated lower-level southerly wind.

Light iron isotopes in high-silica granites record fluid evolution in magmatic-hydrothermal systems - Qi-Wei Li; Qiang Wang; Lin Ma; Andrew C. Kerr; Jing-Jing Fan; Jun-Hong Zhao; Hai-Ou Gu; Wei Wang; Zhi-Kun Su (Geochimica et Cosmochimica Acta, 2025)

Identification, evaluation, control of yellow-causing bacteria and their influence on the quality of high moisture rice-based food - Sijie Zhang; Lin Ou; Cuiping Yi; Qiutao Xie; Yang Shan (Food Control, 2025)

Rapid Video Analysis for Contraction Synchrony of Human Induced Pluripotent Stem Cells-Derived Cardiac Tissues - Yuqing Jiang; Mingcheng Xue; Lu Ou; Huiquan Wu; Jianhui Yang; Wangzihan Zhang; Zhuomin Zhou; Qiang Gao; Bin Lin; Weiwei Kong; Songyue Chen; Daoheng Sun (Tissue Engineering and Regenerative Medicine, 2025)

An in-depth understanding of the role and mechanisms of T cells in immune organ aging and age-related diseases - Yudai Xu; Zijian Wang; Shumin Li; Jun Su; Lijuan Gao; Junwen Ou; Zhanyi Lin; Oscar Junhong Luo; Chanchan Xiao; Guobing Chen (Science China Life Sciences, 2025)

A simple and colorimetric method utilizing cell-free toehold switch sensors for the detection of Chlamydia trachomatis, Ureaplasma urealyticum and Neisseria gonorrhoeae - Fengling Fang; Hongyan Guo; Zhaopei Guo; Lin Lin; Lu Lai; Yue Shi; Weiquan You; Shanjian Chen; Can Liu; Mingming Zhao; Shaobin Guo; Qishui Ou; et al. (Analytica Chimica Acta, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Bioavailability of dissolved organic matter (DOM) derived from seaweed Gracilaria lemaneiformis meditated by microorganisms - Xiao-Li Ou; Lin-Jian Ou; Yu-Feng Yang (Marine Pollution Bulletin, 2024)

Novel application of cyclo(-Phe-Pro) in mitigating aluminum toxicity through oxidative stress alleviation in wheat roots - Yi Wang; Yiqun Ou; Xianyong Lin; Xiaoxia Liu; Chengliang Sun (Environmental Pollution, 2024)

Biomimetic Stylophora pistillata-like NiMoO4/NiFeS crystalline–amorphous phase boundary activated lattice oxygen mechanism for efficient electrochemical water oxidation - Weikai Fan; Chaofan Liu; Jiang Wu; Hao Zhou; Tao Jia; Yang Ling; Ping He; Qunzhi Zhu; Zaiguo Fu; Mingze Ou; Jia lin; Zhongwei Chen (Chemical Engineering Journal, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Validation of the constitution in Chinese medicine questionnaires with the newly developed blood-vacuity category: a rare Taiwanese case study - Ting-Yu Huang; Shi-Chen Ou; Wei-Te Huang; Yu-Chuan Lin; Hao-Hsiu Hung; Chin-Wei Chang; Kai-Yuan Hsiao; Yi-Wei Kao; Chien-Hua Wu; Wei-Shan Chang; Ben-Chang Shia; Sheng-Teng Huang (Advances in Traditional Medicine, 2024)

Security risk assessment of submerged floating tunnel based on fault tree and multistate fuzzy Bayesian network - Dongsheng Qiao; Xiangbo Zhou; Xiangji Ye; Guoqiang Tang; Lin Lu; Jinping Ou (Ocean & Coastal Management, 2024)

Dynamic response analysis of a fully coupled aerodynamic-hydrodynamic-mooring-anchor floating offshore wind turbine - Dongsheng Qiao; Yichen Zhou; Binbin Xu; Jianmin Qin; Guoqiang Tang; Lin Lu; Jinping Ou (Ocean Engineering, 2024)

A general unit hydrograph theory for water level and tidal range distributions in the Modaomen Estuary, China - Bo Li; Huayang Cai; Gaojin Li; Jing Liu; Zhenyan She; Yajun Wang; Suying Ou; Feng Liu; Tongtiegang Zhao; Kairong Lin (Journal of Hydrology, 2024)

Dissection of molecular mechanisms of liver injury induced by microcystin-leucine arginine via single-cell RNA-sequencing - Yunmeng Bai; Yali Song; Miaoran Li; Jinhuan Ou; Hong Hu; Nan Xu; Min Cao; Siyu Wang; Lin Chen; Guangqing Cheng; Zhijie Li; Gang Liu; et al. (Journal of Environmental Sciences, 2024)

Allicin Ameliorated High-glucose Peritoneal Dialysis Solution-induced Peritoneal Fibrosis in Rats via the JAK2/STAT3 Signaling Pathway - Linwang Gan; Lei Geng; Qiancheng Li; Liling Zhang; Yan Huang; Jiaru Lin; Santao Ou (Cell Biochemistry and Biophysics, 2024)

Long-term evolution and controlling factors of tidal duration asymmetry in the mainstream of the Zhujiang River Estuary, China - Shuai Hu; Ping Zhang; Huayang Cai; Suying Ou; Feng Liu; Jianliang Lin; Qingshu Yang (Ocean & Coastal Management, 2024)

Identification of organic constituents on atmospheric particulate matter in the East Asian background air of free troposphere by GC×GC-TOFMS - Chang-Feng Ou-Yang; Yi-Jun Chen; Hsin-Cheng Hsieh; Chung-Te Lee; Kai-Hsien Chi; Neng-Huei Lin; Chih-Chung Chang; Jia-Lin Wang (Chemosphere, 2024)

Influence of tangential hydrodynamic force and inclination angle calculation on the dynamic responses analysis of mooring line based on lumped mass method - Ziming Wang; Dongsheng Qiao; Qingshuai Wu; Guoqiang Tang; Lin Lu; Jinping Ou (Ocean & Coastal Management, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Caspase-8 promotes NLRP3 inflammasome activation mediates eye development defects in zebrafish larvae exposed to perfulorooctane sulfonate (PFOS) - Lu-Yin Wu; Jing-Lin Zhang; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Wan-Ting He; Nanxiang Jin; Ye Dai; Wei Chi; Zejin Ou; Guang-Hui Dong; Li-Zi Lin (Environmental Pollution, 2024)

Salinity threshold for phosphorus limitation in an estuary-coast continuum - Shujie Cai; Weiran Liu; Zhuyin Tong; Lizhen Lin; Linjian Ou; Wupeng Xiao; Bangqin Huang (Frontiers in Marine Science, 2024)
River-derived nutrient imbalances can induce phosphorus (P) limitation in coastal plankton, but the salinity thresholds that govern this phenomenon have received little attention. Here, we provide a first insight into threshold responses in P-limitation along the salinity gradient in coastal ecosystems. Our seasonal sampling in the northern South China Sea showed a clear nonlinear decrease in alkaline phosphatase activity (APA) with increasing salinity. A pivotal finding was the identification of a salinity threshold at 32.83, presenting an early-warning indicator for P-limitation detection. Using a mixed-effects model, we further revealed that the robust positive correlation between phytoplankton biomass and APA gradually weakened as salinity increased toward this threshold. This implies a shift in phytoplankton’s P-limitation at this salinity threshold and the contribution of heterotrophic bacteria in APA within high-salinity seawater. These insights highlight the importance of refining monitoring strategies with salinity and APA dynamics as early-warning indicators for nutrient limitation in coastal ecosystems.

The changes and the potential clinical applications of cytokines in Taiwan’s major venomous snakebites patients - Chih-Chuan Lin; Chia-Cheng Wang; Chun-Hsiang Ou Yang; Chien-Chun Liu; Jau-Song Yu; Wen-Chih Fann; Yen-Chia Chen; Chia-Pang Shih (Toxicon, 2024)

Awakening dumb Mn2+ mechanoluminescence site to achieve force, temperature and time-domain induced color tuning via trap-assisted energy transfer - Jiaqi Ou; Shuangqiang Fang; Haoliang Cheng; Dongjie Han; Qiangqiang Zhu; Yue Zhai; He Lin; Jiali Yu; Renjie Xu; RongJun Xie; Le Wang (Chemical Engineering Journal, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Salinity fronts shape spatial patterns in Zooplankton distribution in Hangzhou Bay - Yepeng Xu; Yiqi Wang; Lin Zhan; Yijun Ou; Kangning Jia; Ming Mao; Xuyu Zhu; Zhibing Jiang; Yuanli Zhu; Wei Huang; Ping Du; Jiangning Zeng; et al. (Acta Oceanologica Sinica, 2024)

Annual mapping of Spartina alterniflora with deep learning and spectral-phenological features from 2017 to 2021 in the mainland of China - Xiarong Li; Jinyan Tian; Xiaojuan Li; Yongxin Yu; Yang Ou; Lin Zhu; Xiumin Zhu; Bingfeng Zhou; Huili Gong (International Journal of Remote Sensing, 2024)

Implementing policies to mitigate urban heat islands: Analyzing urban development factors with an innovative machine learning approach - Shiang-Yu Wang; Hsing-Yu Ou; Ping-Chun Chen; Tzu-Ping Lin (Urban Climate, 2024)

Monitoring system framework design for floating wind turbine using the deep learning technology and tower response identification considering sensor optimization - Ziming Wang; Dongsheng Qiao; Guoqiang Tang; Lin Lu; Jinping Ou (Ocean Engineering, 2024)

Fractional nutrient uptake model of plant roots - Yue Wang; Mingfang Lin; Quanbiao Gong; Zhonghui Ou (BioSystems, 2024)

Evaluation of the Efficacy of Stem Cells Therapy in the Periodontal Regeneration: A Meta-Analysis and Mendelian Randomization Study - Jing Hu; Ze-Yue Ou-Yang; Ya-Qiong Zhao; Jie Zhao; Li Tan; Qiong Liu; Min-yuan Wang; Qin Ye; Yao Feng; Meng-Mei Zhong; Ning-Xin Chen; Xiao-Lin Su; et al. (Stem Cell Reviews and Reports, 2024)

The biocontrol potentials of rhizospheric bacterium Bacillus velezensis K0T24 against mulberry bacterial wilt disease - Wenlian Jiao; Ju Wen; Na Li; Ting Ou; Changyu Qiu; Yutong Ji; Kai Lin; Xiaojiao Liu; Jie Xie (Archives of Microbiology, 2024)

Organic nutrient availability and extracellular enzyme activities influence harmful algal bloom proliferation in a coastal aquaculture area - Lin-Jian Ou; Zhou Wang; Guang-Mao Ding; Feng-Xian Han; Jin-Yi Cen; Xin-Feng Dai; Ke-Qiang Li; Song-Hui Lu (Aquaculture, 2024)

Neurological impairment is crucial for tire rubber-derived contaminant 6PPDQ-induced acute toxicity to rainbow trout - Xiao-Liang Liao; Zhi-Feng Chen; Shi-Ping Ou; Qian-Yi Liu; Shan-Hong Lin; Jia-Ming Zhou; Yujie Wang; Zongwei Cai (Science Bulletin, 2024)

Significance of phosphate adsorbed on the cellular surface as a storage pool and its regulation in marine microalgae - Xian-Yang Zhang; Zhuo-Fan Li; Hai-Feng Gu; Ai-Qin Han; Feng-Xian Han; Lin-Jian Ou (Marine Environmental Research, 2024)

Co dopant anchored in the BiOIO3 nanosheets to induce oxygen vacancies for enhanced photocatalytic activity - Mao Lin; Hailong Liu; Hairong Wang; Jiang Wu; Haoyu Jiang; Hao Wei; Mingze Ou; Zhenzhen Guan; Zhuoxin Dong; Jiarun Qi (Chemical Engineering Journal, 2024)

On the formation of postnoon auroral bright spots during weak substorm activity - Su Zhou; Yongzhi Cai; Ping Ou; Lin Zhu; Dan Wu (Advances in Space Research, 2024)

Membrane lipid remodeling and autophagy to cope with phosphorus deficiency in the dinoflagellate Prorocentrum shikokuense - Da-Wei Li; Jin-Zhou Tan; Zhuo-Fan Li; Lin-Jian Ou (Chemosphere, 2024)

Role of covalent modification by hepatic aldehydes in dictamnine-induced liver injury - Qi Luo; Yang Shen; Guohong Zhai; Lin Chen; Furong Ou; Luxi Yi; Danli Yang; Hong Pan; Fuguo Shi (Toxicology Letters, 2024)

Efficient and cost-effective method for identifying urban ventilation corridors using a heuristic search algorithm - Tsz-Kin Lau; Pei-Chi Tsai; Hsing-Yu Ou; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

The associations of secondhand smoke exposure with neurodevelopmental disorders and critical time window identification: A systematic review and meta-analysis - Xiao-Xuan Ou; Xin Wang; Xiao-Ling Zhan; Shu-Li Shen; Shamshad Karatela; Jin Jing; Li Cai; Ru-Qing Liu; Li-Zi Lin; Guang-Hui Dong (Science of The Total Environment, 2024)

Enhancement of coal tar pitch carbonization with biochar: A metallurgical formed biocoke product produced by waste coke breeze and bamboo powder - Lin Wang; Yongbin Yang; Yang Ou; Yinrui Dong; Qiang Zhong; Yan Zhang; Qian Li; Zhucheng Huang; Tao Jiang (Fuel, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Synergistic conversion of iron ore sintering dust and waste biochar to produce direct reduction iron and syngas: Gasification, reduction behavior and thermodynamic analysis - Lin Wang; Yongbin Yang; Yang Ou; Peiyao Tang; Chen Liu; Qiang Zhong; Yan Zhang; Lingyun Yi; Qian Li; Zhucheng Huang; Tao Jiang (Journal of Cleaner Production, 2024)

The potential mechanism of concentrated mannan-oligosaccharide promoting goldfish’s (Carassius auratus Linnaeus) resistance to Ichthyophthirius multifiliis invasion - Senyue Liu; Ming Xu; Baipeng Chen; Fulong Li; Yongqiang Deng; Yufan Zhang; Gang Lin; Defang Chen; Yi Geng; Yangping Ou; Xiaoli Huang (Fish & Shellfish Immunology, 2024)

Possibility of condensation of nitric acid for cloud condensation nucleus in the summer at Mt. Fuji - Kojiro Shimada; Yoshun Geka; Shungo Kato; Chak K. Chan; Yong Pyo Kim; Chang-Feng Ou-Yang; Neng-Huei Lin; Shiro Hatakeyama (Atmospheric Pollution Research, 2024)

Building a predictive model for hypertension related to environmental chemicals using machine learning - Shanshan Liu; Lin Lu; Fei Wang; Bingqing Han; Lei Ou; Xiangyang Gao; Yi Luo; Wenjing Huo; Qiang Zeng (Environmental Science and Pollution Research, 2023)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

Application of novel nanobubble-contained electrolyzed catalytic water to cleanup petroleum-hydrocarbon contaminated soils and groundwater: A pilot-scale and performance evaluation study - Wing-Sze Ho; Wei-Han Lin; Francis Verpoort; Kun-Liang Hong; Jiun-Hau Ou; Chih-Ming Kao (Journal of Environmental Management, 2023)

Synergistic recycling of biochar from sawdust pyrolysis and waste coke breeze to produce metallurgical quality biocoke with syngas as a by-product - Lin Wang; Yongbin Yang; Yang Ou; Qiang Zhong; Peiyao Tang; Yan Zhang; Lingyun Yi; Qian Li; Zhucheng Huang; Tao Jiang (Fuel, 2023)

Deployment priority of public charging speeds for increasing battery electric vehicle usability - Wan Li; Zhenhong Lin; Shiqi(Shawn) Ou; Boyu Wang (Transportation Research Part D: Transport and Environment, 2023)

Characterization of anglerfish gelatin/polyvinyl alcohol film and its application in preservation of small yellow croaker (Larimichthys polyactis) - Bing Lin; Xiaojun Zhang; Duipeng Ou; Yu Chen; Yunyun Chen; Xuechang Chen (Journal of Food Engineering, 2023)

Variation in intracellular polyphosphate and associated gene expression in response to different phosphorus conditions in the dinoflagellate Karenia mikimotoi - Wen-Yu Jin; Xiang-Wu Chen; Jin-Zhou Tan; Xin Lin; Lin-Jian Ou (Harmful Algae, 2023)

Assessment of microplastic contamination in an eastern Pacific tuna (Katsuwonus pelamis) and evaluation of its health risk implication through molecular docking and metabolomics studies - Lijun Wu; Xiaojie Dai; Jing Xu; Danyun Ou; Lei Wang; Hui Lin; Weiyi He; Haitao Lin; Rupeng Du; Hao Huang; Weiwen Li; Zhong Pan (Food Chemistry, 2023)

Dextran-based micelles for combinational chemo-photodynamic therapy of tumors via in vivo chemiluminescence - Chendi Ding; Zhaoqing Shi; Meitong Ou; Yingbang Li; Li Huang; Wenyan Wang; Qili Huang; Meihang Li; Chunbo Chen; Xiaowei Zeng; Hongzhong Chen; Lin Mei (Carbohydrate Polymers, 2023)

Using drone soundings to study the impacts and compositions of plumes from a gigantic coal-fired power plant - Yen-Chen Chen; Jia-Lin Wang; Chih-Yuan Chang; Ming-Tung Chuang; Charles C.-K. Chou; Xiang-Xu Pan; Yu-Jui Ho; Chang-Feng Ou-Yang; Wen-Tzu Liu; Chih-Chung Chang (Science of The Total Environment, 2023)

Recycling of subducted Indian continental crust constrained by late Cretaceous mafic dykes in Central Lhasa block of the Tibetan plateau - Lu-Lu Hao; Andrew C. Kerr; Qiang Wang; Lin Ma; Yue Qi; Ming Xiao; Quan Ou (Lithos, 2023)

Photothermal-assisted for ultrafast response acetone sensing with ZIF-90/GO coated microfiber long period gratings - Yan Huang; Wenfu Lin; Ziruo Zhang; Zhenru Li; Tiansheng Huang; Jie Li; Li-Peng Sun; Bai-Ou Guan (Chemical Engineering Journal, 2023)

High-performance peptide and disulfide mapping by direct injection of intact proteins using on-line coupled UV-liquid chromatography microdroplet mass spectrometry (UVLC-MMS) - Chin-Ming Kuo; Hung-Hsiang Jen; Fung-Yu Chen; Mohsen Akbarian; Tai-Hong Ou; Kang-Yu Liu; Jung-Lee Lin; Shu-Hui Chen (Analytica Chimica Acta, 2023)

A clean and efficient innovative technology for refractory sulfide gold ore: In situ gold extraction via self-generated thiosulfate - Yang Ou; Yongbin Yang; Lin Wang; Ke Li; Wei Gao; Yan Zhang; Qian Li; Tao Jiang (Journal of Cleaner Production, 2023)

Effects of orientation and dimensions of shading structures on thermal comfort - Hsing-Yu Ou; Tzu-Ping Lin (Building and Environment, 2023)

Wet bias of summer precipitation in the northwestern Tibetan Plateau in ERA5 is linked to overestimated lower-level southerly wind over the plateau - Tinghai Ou; Deliang Chen; Jianping Tang; Changgui Lin; Xuejia Wang; Julia Kukulies; Hui-Wen Lai (Climate Dynamics, 2023)
The Tibetan Plateau (TP), also called the Third Pole, is considered to be “the world water tower”. The northwestern TP (NWTP), which has an average elevation higher than 4800 m, is an arid region where the summer precipitation is largely overestimated by the ERA5 global reanalysis product. We hypothesize that this wet bias is mainly caused by unrealistic lower-level winds that trigger strong convection over the region; it can be reduced by using a high-resolution regional climate model with a large domain that allows realistically representing interactions between the Westerlies and Asian summer monsoons. Here, downscaling using the Weather Research and Forecasting (WRF) model driven by ERA5 was conducted with a large domain (8°‒50° N, 65°‒125° E) at 9 km for the period 1979‒2019 (WRF9km). Precipitation values from WRF9km and ERA5 were evaluated against satellite observations; compared with ERA5, WRF9km captured the climatological summer precipitation over the NWTP with a much-reduced wet bias. The ERA5 overestimation is mainly caused by excessive convective precipitation, likely linked to strong vertical motions over the NWTP induced by an overestimated lower-level southerly wind.

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

Cleanup of Cr(VI)-polluted groundwater using immobilized bacterial consortia via bioreduction mechanisms - Wei-Han Lin; Chih-Ching Chien; Jiun-Hau Ou; Ying-Liang Yu; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2023)

Preparation of formed coke product as a coke substitute using a solid waste fuel: Trimethylbenzene improvement on coal tar pitch - Lin Wang; Yongbin Yang; Yang Ou; Peiyao Tang; Chen Liu; Xiaoxuan Zhang; Qiang Zhong; Qian Li; Tao Jiang (Fuel, 2023)

Stem Cell Therapy in Spinal Cord Injury-Induced Neurogenic Lower Urinary Tract Dysfunction - Yin-Chien Ou; Chi-Chen Huang; Yao-Lin Kao; Pei-Chuan Ho; Kuen-Jer Tsai (Stem Cell Reviews and Reports, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Succession of microbial communities with VOC changes during composting process - Tachen Lin; Yunlong Zhao; Yuan Jiang; Jinlan Ou; Adnan Hussain; Lixian Chen; Chitsan Lin (Bioresource Technology Reports, 2023)

Deletion of the cheZ gene results in the loss of swimming ability and the decrease of adhesion ability to Caco-2 cells in Escherichia coli Nissle 1917 - Bingming Ou; Haihui Lv; Hua Ge; Dexiang Fu; Xin Lin; Saiqiao Huang; Xiaojie Chen; Yufu Liu; Sainan Li; Wenhua Liu; Lihua Huang; Ying Yang; et al. (Folia Microbiologica, 2023)

Long-term exposure to ambient air pollution, circadian syndrome and cardiovascular disease: A nationwide study in China - Xiangming Hu; Zhiqiang Nie; Yanqiu Ou; Lizi Lin; Zhengmin Qian; Michael G. Vaughn; Stephen Edward McMillin; Yingling Zhou; Yongjian Wu; Guanghui Dong; Haojian Dong (Science of The Total Environment, 2023)

Donor-acceptor engineered g-C3N4 enabling peroxymonosulfate photocatalytic conversion to 1O2 with nearly 100% selectivity - Zonglin Weng; Yuanfang Lin; Bin Han; Xinfei Zhang; Qin Guo; Yu Luo; Xinwen Ou; Yang Zhou; Jin Jiang (Journal of Hazardous Materials, 2023)

Rational design of donor-acceptor engineered g-C3N4 for boosted H2O2 production via photocatalytic O2 reduction - Yu Luo; Yuanfang Lin; Zonglin Weng; Bin Han; Yang Zhou; Xinwen Ou; Jin Jiang (Journal of Environmental Chemical Engineering, 2023)

Assessment of exhaled pathogenic droplet dispersion and indoor-outdoor exposure risk in urban street with naturally-ventilated buildings - Jian Hang; Xia Yang; Cui-Yun Ou; Zhi-Wen Luo; Xiao-Dan Fan; Xue-Lin Zhang; Zhong-Li Gu; Xian-Xiang Li (Building and Environment, 2023)

Development of Nafion/single-walled carbon nanotube integrated arrays for the rapid detection of salbutamol doping - Yingshiyu Lin; Lingbo Liu; Gaozhi Ou; Wensheng Huang; Kangbing Wu (Analytica Chimica Acta, 2023)

Complete genome of Sphingomonas paucimobilis ZJSH1, an endophytic bacterium from Dendrobium officinale with stress resistance and growth promotion potential - Jin Li; Hangtao Wu; Qian Pu; Chu Zhang; Ying Chen; Zhengxin Lin; Xiufang Hu; Ou Li (Archives of Microbiology, 2023)

Low-crystalline Ni(OH)2 ultrathin nanosheets upcycled from solid wastes for efficient photoconversion of low-concentration CO2 - Bin Han; Yuanfang Lin; Yu Luo; Weizhen Liu; Xueming Liu; Zonglin Weng; Xinwen Ou; Zhang Lin (Chemical Engineering Journal, 2023)

Analytical solution of Nye–Tinker–Barber model by Laplace transform - Yue Wang; Wenting Lin; Zhonghui Ou (BioSystems, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Lipid peroxide-derived short-chain aldehydes promote programmed cell death in wheat roots under aluminum stress - Xin Liang; Ruyi Qian; Yiqun Ou; Dan Wang; Xianyong Lin; Chengliang Sun (Journal of Hazardous Materials, 2023)

Eco-friendly and low-energy innovative scheme of self-generated thiosulfate by atmospheric oxidation for green gold extraction - Yang Ou; Yongbin Yang; Ke Li; Wei Gao; Lin Wang; Qian Li; Tao Jiang (Journal of Cleaner Production, 2023)

CH4 and CO2 emissions in water networks of rice cultivation regions - Ouping Deng; Jiangyou Ran; Xuesong Gao; Xiangjun Lin; Ting Lan; Ling Luo; Yalan Xiong; Jiang Liu; Dinghua Ou; Jianbo Fei; Rong Huang (Environmental Research, 2023)

Enhancement of the wettability of a coal seam during water injection: effect and mechanism of surfactant concentrations above the CMC - Tianyang Wang; Jianguo Liu; Shu Wang; Longzhe Jin; Minglei Lin; Shengnan Ou (Environmental Science and Pollution Research, 2023)

Using habitat classification and large-scale spatial planning model to identify environmental areas: A case study in the area of the Northwest Pacific Ocean - Huang Hao; Cai Lei; Lei Wang; Weiwen Li; Ou Danyun; Wu Lijun; Ou Rimei; Lin Lianghua (Marine Policy, 2023)

Triclosan in paired-maternal and cord blood, and their relationships with congenital heart disease of baby - Yu-Ling Luan; Yan-Qiu Ou; Xiao-Qing Liu; Shao Lin; Ying Guo (Science of The Total Environment, 2023)

Infusing satellite data into aerosol forecast for near real-time episode detection and diagnosis in East Asia - Sheng-Po Chen; Cheng-Hsuan (Sarah) Lu; James E. Davies; Chang-Feng Ou-Yang; Neng-Huei Lin; Amy K. Huff; Bradley R. Pierce; Shobha Kondragunta; Jia-Lin Wang (Science of The Total Environment, 2023)

A method for determining optimal electric range by considering electric vehicle lightweighting on perceived ownership cost - Shiqi Ou; Shengyong Zhang; Zhenhong Lin; Stacy Davis (Journal of Cleaner Production, 2023)

Feasibility analysis of resource application of waste incineration fly ash in asphalt pavement materials - Xiaolong Sun; Zhixin Ou; Qin Xu; Xiao Qin; Yongchang Guo; Jiaxiang Lin; Junshen Yuan (Environmental Science and Pollution Research, 2023)

Integrative analysis uncovers response mechanism of Pirata subpiraticus to chronic cadmium stress - Ou-lin Dai; Zi-yan Lei; Yuan-de Peng; Zhi Wang (Environmental Science and Pollution Research, 2022)

Age, Growth and Population Structure Analyses of the Purpleback Flying Squid Sthenoteuthis oualaniensis in the Northwest Indian Ocean by the Statolith Microstructure - Yu-Zhe Ou; Hua-Jie Lu; Hong-Hao Wang; Zi-Yue Chen; Mao-Lin Zhao (Fishes, 2022)
A total of 1177 Sthenoteuthis oualaniensis were randomly collected from the northwest Indian Ocean from February between May 2019 and 2020 by lighting falling-net vessels. The age, growth, and population structure of S. oualaniensis were studied based on the statolith microstructure. The results showed that the range of mantle length (ML) was 123–562 mm for females and 88–273 mm for males, and the range of body weight (BW) was 78–6268 g for females and 82–518 g for males in 2019 and 2020, respectively. The hatching date extended from May to December, with the 2019 samples mainly composed of the autumn population, while the 2020 samples were mostly composed of the summer population. The analysis of covariance (ANCOVA) showed that there were significant differences in the growth of ML–age and BW–age between sexes. In the growth model of the ML–age relationship, both females and males in 2019 were best described by s linear model, and 2020 was best described by a logarithmic model. The growth model of the BW–age relationship of females and males in 2019 was best described as linear and the growth model of the BW–age relationship of females and males in 2020 was described logarithmically and exponentially, respectively. The average absolute daily growth rate (AGR) and instantaneous growth rate (IGR) for ML of the 2019 samples were 0.85 mm/d and 0.40%/d, and the average AGR and IGR for ML of the 2020 samples were 0.65 mm/d and 0.18%, respectively. The growth of S. oualaniensis samples in 2019 was faster than that in 2020. This study provided basic information on the age, growth, and population of S. oualaniensis, which will supply a scientific basis for stock assessment and sustainable development.

Analysis of the Mechanism of Water Inrush Geohazards in Deep-Buried Tunnels under the Complex Geological Environment of Karst Cave-Fractured Zone - Weishe Zhang; Yuyong Jiao; Guohua Zhang; Xi Zhang; Guangzhao Ou; Zhiping Lin (Journal of Earth Science, 2022)

Age, Growth and Population Structure Analyses of the Purpleback Flying Squid Sthenoteuthis oualaniensis in the Northwest Indian Ocean by Beak Microstructure - Hua-Jie Lu; Yu-Zhe Ou; Jing-Ru He; Mao-Lin Zhao; Zi-Yue Chen; Xin-Jun Chen (Journal of Marine Science and Engineering, 2022)
To explore the feasibility of using beak microstructure information to estimate the age of Sthenoteuthis oualaniensis, the microstructures of the upper beaks of individual squid were applied in this work to analyze the ages and growth patterns of squid caught from February–May 2019 and from October–December 2020 in the northwest Indian Ocean. The results indicated that the squid samples in the two years were no older than 9 months, and the samples in 2019 were autumn population and 2020 were spring population. The linear growth model of the autumn population (2019) was the best model for describing the relationship between age and ML, while the power model of the spring population (2020) was the best for describing the relationship between age and ML. The maximum instantaneous growth rate (IGR) and absolute daily growth rate (AGR) values of the spring population were 0.24%/d and 1.09 mm/d, respectively, occurring in squid between 200 and 220 days of age. The maximum IGR and AGR values of the autumn population were 0.69%/d and 1.73 mm/d, respectively, occurring in squid between 200 and 240 days of age. The period from 141–260 days (5–8 months) was considered to correspond to the subadult stage in the whole life history of S. oualaniensis in the Northwest Indian Ocean. The beak microstructure information can be effectively applied to estimate the age of S. oualaniensis individuals.

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Short-term variations and influencing factors of suspended sediment concentrations at the Heisha Beach, Guangdong, China - Jintang Ou; Haoyan Dong; Liangwen Jia; Xiangxin Luo; Zixiao He; Kanglin Chen; Jing Liu; Yitong Lin; Mingdong Yu; Mingen Liang (Acta Oceanologica Sinica, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Individual exposure to ambient PM2.5 and hospital admissions for COPD in 110 hospitals: a case-crossover study in Guangzhou, China - Jie-Qi Jin; Dong Han; Qi Tian; Zhao-Yue Chen; Yun-Shao Ye; Qiao-Xuan Lin; Chun-Quan Ou; Li Li (Environmental Science and Pollution Research, 2022)
Few studies have evaluated the short-term association between hospital admissions and individual exposure to ambient particulate matter (PM 2.5 ). Particularly, no studies focused on hospital admissions for chronic obstructive pulmonary disease (COPD) at the individual level. We assessed the short-term effects of PM 2.5 on hospitalization admissions for COPD in Guangzhou, China, during 2014–2015, based on satellite-derived estimates of ambient PM 2.5 concentrations at a 1-km resolution near the residential address as individual-level exposure for each patient. Around 40,002 patients with COPD admitted to 110 hospitals were included in this study. A time-stratified case-crossover design with conditional logistic regression models was applied to assess the effects of PM 2.5 based on a 1-km grid data of aerosol optical depth provided by the National Aeronautics and Space Administration on hospital admissions for COPD. Further, we performed stratified analyses by individual demographic characteristics and season of hospital admission. Around 10 μg/m 3 increase in individual-level PM 2.5 was associated with an increase of 1.6% (95% confidence interval [CI]: 0.6%, 2.7%) in hospitalization for COPD at a lag of 0–5 days. The impact of PM 2.5 on hospitalization for COPD was greater significantly in males and patients admitted in summer. Our study strengthened the evidence for the adverse effect of PM 2.5 based on satellite-based individual-level exposure data.

Enhancement of aqueous stability of NH2-MIL-101(Fe) by hydrophobic grafting post-synthetic modification - Jianwei Fu; Lin Wang; Yuheng Chen; Deyi Yan; Huase Ou (Environmental Science and Pollution Research, 2021)

Sodium P-aminosalicylic Acid Attenuates Manganese-Induced Neuroinflammation in BV2 Microglia by Modulating NF-κB Pathway - Junyan Li; Yue Deng; Dongjie Peng; Lin Zhao; Yuanyuan Fang; Xiaojuan Zhu; Shaojun Li; Michael Aschner; Shiyan Ou; Yueming Jiang (Biological Trace Element Research, 2021)

Effects of organic matter on the distribution of rare earth elements in red soil aggregates during ecological restoration - Xiao-lin Ou; Zhi-biao Chen; Zhi-qiang Chen; Mei-xia Liang; Hai-bin Chen (Journal of Mountain Science, 2021)

Protective Effects of Sodium Para-aminosalicylic Acid on Manganese-Induced Damage in Rat Pancreas - Xiaojuan Zhu; Bingyan Xie; Dianyin Liang; Wenxia Qin; Lin Zhao; Yue Deng; Pingjing Wen; Fang Xu; Michael Aschner; Yueming Jiang; Shiyan Ou (Biological Trace Element Research, 2021)

Sodium P-aminosalicylic Acid Inhibits Manganese-Induced Neuroinflammation in BV2 Microglial Cells via NLRP3-CASP1 Inflammasome Pathway - Yuanyuan Fang; Dongjie Peng; Yuan Liang; Lili Lu; Junyan Li; Lin Zhao; Shiyan Ou; Shaojun Li; Michael Aschner; Yueming Jiang (Biological Trace Element Research, 2021)

Associations of Sleep Characteristics with Cerebrospinal Fluid sTREM2 in Cognitively Normal Older Adults: the CABLE Study - He-Ying Hu; Ling-Zhi Ma; Hao Hu; Yan-Lin Bi; Ya-Hui Ma; Xue-Ning Shen; Ya-Nan Ou; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Late Jurassic Maofengshan two‐mica granites in Guangzhou, South China: fractional crystallization products of metasedimentary‐rock‐derived magmas - Xiao Liu; Qiang Wang; Lin Ma; Guo-Ning Gou; Quan Ou; Jun Wang (Mineralogy and Petrology, 2021)

Changes in arthropod community but not plant quality benefit a specialist herbivore on plants under reduced water availability - Po-An Lin; Chia-Ming Liu; Jia-Ang Ou; Cheng-Han Sun; Wen-Po Chuang; Chuan-Kai Ho; Natsuko Kinoshita; Gary W. Felton (Oecologia, 2021)

Liver Function of Male Rats Exposed to Manganese at Different Time Points - Xiaonian Zhu; Lin Yang; Yonghua He; Yi Sun; Wenxiang Shi; Chaoyan Ou (Biological Trace Element Research, 2020)

On the mechanism of soft clay being improved entirely in the ECT treatment - Chang-Yu Ou; Chien-Yu Lin; Shao-Chi Chien (Bulletin of Engineering Geology and the Environment, 2020)

Correlations Between Skin Barrier Integrity and Delivery of Hydrophilic Molecules in the Presence of Penetration Enhancers - XueKe Lin; ZhenHua Wang; HuiLong Ou; Samir Mitragotri; Ming Chen (Pharmaceutical Research, 2020)

Simulation of summer precipitation diurnal cycles over the Tibetan Plateau at the gray-zone grid spacing for cumulus parameterization - Tinghai Ou; Deliang Chen; Xingchao Chen; Changgui Lin; Kun Yang; Hui-Wen Lai; Fuqing Zhang (Climate Dynamics, 2020)
The Tibetan Plateau (TP) is often referred to as the “water tower of Asia” or the “Third Pole”. It remains a challenge for most global and regional models to realistically simulate precipitation, especially its diurnal cycles, over the TP. This study focuses on evaluating the summer (June–August) precipitation diurnal cycles over the TP simulated by the Weather Research and Forecasting (WRF) model. The horizontal resolution used in this study is 9 km, which is within the gray-zone grid spacing that a cumulus parameterization scheme (CU) may or may not be used. We conducted WRF simulations with different cumulus schemes (CU experiments) and a simulation without CU (No_CU experiment). The selected CUs include the Grell-3D Ensemble (Grell), New Simplified Arakawa-Schubert (NSAS), and Multiscale Kain-Fritsch (MSKF). These simulations are compared with both the in-situ observations and satellite products. Results show that the scale-aware MSKF outperforms the other CUs in simulating precipitation in terms of both the mean intensity and diurnal cycles. In addition, the peak time of precipitation intensity is better captured by all the CU experiments than by the No_CU experiment. However, all the CU experiments tend to overestimate the mean precipitation and simulate an earlier peak of precipitation frequency when compared to observations. The frequencies and initiation timings for short-duration (1–3 h) and long-duration (> 6 h) precipitation events are well captured by the No_CU experiment, while these features are poorly reproduced by the CU experiments. The results demonstrate simulation without a CU outperforms those with a CU at the gray-zone spatial resolution in regard to the precipitation diurnal cycles.

Intensity and daily pattern of passenger vehicle use by region and class in China: estimation and implications for energy use and electrification - Shiqi Ou; Rujie Yu; Zhenhong Lin; Huanhuan Ren; Xin He; Steven Przesmitzki; Jessey Bouchard (Mitigation and Adaptation Strategies for Global Change, 2020)

Sarocladium species associated with rice in Taiwan - Jie-Hao Ou; Guo-Cih Lin; Chi-Yu Chen (Mycological Progress, 2020)

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Integrated analysis of quantitative proteome and transcriptional profiles reveals abnormal gene expression and signal pathway in bladder cancer - Songbai Liao; Minglin Ou; Liusheng Lai; Hua Lin; Yaoshuang Zou; Yonggang Yu; Xuede Li; Yong Dai; Weiguo Sui (Genes & Genomics, 2019)

Remediation of TCE-contaminated groundwater using KMnO4 oxidation: laboratory and field-scale studies - Zong-Han Yang; Jiun-Hau Ou; Cheng-Di Dong; Chiu-Wen Chen; Wei-Han Lin; Chih-Ming Kao (Environmental Science and Pollution Research, 2019)

Immunological microenvironment alterations in follicles of women with proven severe endometriosis undergoing in vitro fertilization - Xiao-Dan Mao; Chen-Yu Hu; Meng-Chu Zhu; Hui-Lin Ou; Yu-Li Qian (Molecular Biology Reports, 2019)

STAT3-induced SMYD3 transcription enhances chronic lymphocytic leukemia cell growth in vitro and in vivo - Fujia Lin; Danjuan Wu; Dan Fang; Yao Chen; Haitao Zhou; Caiwen Ou (Inflammation Research, 2019)

Detection and quantification of Aeromonas schubertii in Channa maculata by TaqMan MGB probe fluorescence real‐time quantitative PCR - Chun Liu; Yanming M. Guo; Jizhen Z. Cao; De‐Feng Zhang; Ou‐Qin Chang; Kaibin Li; Fang Wang; Cun‐Bin Shi; Lan Jiang; Qing Wang; Li Lin (Journal of Fish Diseases, 2019)
Aeromonas schubertii is a major epidemiological agent that threatens cultured snakeheads ( Channidae ) and has caused great economic losses in fish‐farming industries in China in recent years. In present study, a specific TaqMan minor groove binder ( MGB ) probe fluorescence real‐time quantitative PCR ( qPCR ) assay was developed to rapidly detect and quantify A. schubertii . A pair of qPCR primers and a TaqMan MGB probe were selected from the rpoD gene, which were shown to be specific for A. schubertii . A high correlation coefficient ( R 2 = 0.9998) in a standard curve with a 103% efficiency was obtained. Moreover, the qPCR method's detection limit was as low as 18 copies/μl, which was 100 times more sensitive than that of conventional PCR . The detection results for the A. schubertii in pond water and fish tissue were consistent with those of the viable counts. Bacterial load changes detected by qPCR in different tissues of snakeheads infected with A. schubertii showed that the gills and intestines may be the entry for A. schubertii , and the spleen and kidney are major sites for A. schubertii replication. The established method in present study should be a useful tool for the early surveillance and quantitation of A. schubertii .

A new perspective on solar dimming over the Tibetan Plateau - Changgui Lin; Huanping Wu; Tinghai Ou; Deliang Chen (International Journal of Climatology, 2019)
Solar radiation changes (dimming/brightening) have recently received growing attention within the research community, although there is currently no generally accepted explanation. This article aims to provide a new perspective for identifying the reasons behind solar dimming/brightening by using long‐term measurements of direct and diffuse solar radiation, unlike previous studies which have focused on global solar radiation. We postulate that extinction processes can be more readily revealed by direct and diffuse radiation measurements with the help of a modelling tool that treats the two components separately. An example is presented for Golmud and Lhasa in the northern and southern Tibetan Plateau (TP) respectively, over the period 1957–2013. The following is found: (a) ground‐based observed cloud cover alone hardly explains the observed solar dimming at the two sites; (b) both the cloud‐free direct radiation transmittivity ( τ dir ) and diffuse radiation proportion ( p dif ) declined; (c) variations in p dif are overwhelmingly dominated by variations in aerosols, while those in τ dir are related to variations in both aerosol and water vapour; (d) on top of the suggested reduced aerosol concentrations, decreased snow cover can partly explain declined diffuse radiation via lowered surface albedo; (e) the decline in τ dir can be partly attributed to the wetting atmosphere via strengthened absorption; and (f) the impact of volcanic eruptions was also identified from such radiative parameters, lasting into the following summer and especially strong in the southern TP.

Impact of model resolution on simulating the water vapor transport through the central Himalayas: implication for models’ wet bias over the Tibetan Plateau - Changgui Lin; Deliang Chen; Kun Yang; Tinghai Ou (Climate Dynamics, 2018)

A large meta-analysis of the global prevalence rates of S. aureus and MRSA contamination of milk - Qianting Ou; Junli Zhou; Dongxin Lin; Chan Bai; Ting Zhang; Jialing Lin; Haoqu Zheng; Xiaojie Wang; Jiaping Ye; Xiaohua Ye; Zhenjiang Yao (Critical Reviews in Food Science and Nutrition, 2018)

Whole-genome sequence and genome annotation of Xanthomonas citri pv. mangiferaeindicae, causal agent of bacterial black spot on Mangifera indica - Feng Liu; Xiong-chang Ou; Ru-lin Zhan (Archives of Microbiology, 2018)

Identification of the dwarf gene GmDW1 in soybean (Glycine max L.) by combining mapping-by-sequencing and linkage analysis - Zhong-feng Li; Yong Guo; Lin Ou; Huilong Hong; Jun Wang; Zhang-xiong Liu; Bingfu Guo; Lijuan Zhang; Lijuan Qiu (Theoretical and Applied Genetics, 2018)

Correction to: Age at menarche and age at natural menopause in East Asian women: a genome-wide association study - Jiajun Shi; Ben Zhang; Ji-Yeob Choi; Yu-Tang Gao; Huaixing Li; Wei Lu; Jirong Long; Daehee Kang; Yong-Bing Xiang; Wanqing Wen; Sue K. Park; Xingwang Ye; et al. (GeroScience, 2018)

Robust multiple update-rate Kalman filter for new generation navigation signals carrier tracking - Honglei Lin; Yangbo Huang; Xiaomei Tang; Zhibin Xiao; Gang Ou (GPS Solutions, 2018)

Effects of live rock on removal of dissolved inorganic nitrogen in coral aquaria - Yan Li; Xinqing Zheng; Xiaozhou Yang; Dangyun Ou; Rongcheng Lin; Xinming Liu (Acta Oceanologica Sinica, 2017)

Adsorption-Desorption Characteristics of Nonylphenol on Two Different Origins of Black Carbon - Guanghuan Cheng; Mingyang Sun; Xinlei Ge; Yang Ou; Xinhua Xu; Qi Lin; Liping Lou (Water, Air, & Soil Pollution, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Future Science Prize goes to non-invasive prenatal testing - Kang Li; Yaou Duan; Magdalene Yin Lin Ting; Zhiying Ou; Li Liu; Kang Zhang; Xin Fu (Science China Life Sciences, 2017)

Retraction Note to: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2017)

Effectiveness and intermediates of microcystin-LR degradation by UV/H2O2 via 265 nm ultraviolet light-emitting diodes - Juan Liu; Jin-shao Ye; Hua-se Ou; Jialing Lin (Environmental Science and Pollution Research, 2017)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Mechanical Behavior of Brittle Rock-Like Specimens with Pre-existing Fissures Under Uniaxial Loading: Experimental Studies and Particle Mechanics Approach - Ri-hong Cao; Ping Cao; Hang Lin; Cheng-zhi Pu; Ke Ou (Rock Mechanics and Rock Engineering, 2016)

DNA Methylation Changes Induced in Rice by Exposure to High Concentrations of the Nitric Oxide Modulator, Sodium Nitroprusside - Xiufang Ou; Tingting Zhuang; Wenchao Yin; Yiling Miao; Bo Wang; Yunhong Zhang; Xiuyun Lin; Chunming Xu; Diter von Wettstein; Sachin Rustgi; Bao Liu (Plant Molecular Biology Reporter, 2015)

Retraction Note to: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2015)

RETRACTED ARTICLE: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2015)

Contamination of sulfonamide antibiotics and sulfamethazine-resistant bacteria in the downstream and estuarine areas of Jiulong River in Southeast China - Danyun Ou; Bin Chen; Renao Bai; Puqing Song; Heshan Lin (Environmental Science and Pollution Research, 2015)

Genome-Wide Identification of microRNAs and Their Targets in Cold-Stored Potato Tubers by Deep Sequencing and Degradome Analysis - Yongbin Ou; Xun Liu; Conghua Xie; Huiling Zhang; Yuan Lin; Meng Li; Botao Song; Jun Liu (Plant Molecular Biology Reporter, 2015)

l-Amino acid carbamate prodrugs of scutellarin: synthesis, physiochemical property, Caco-2 cell permeability, and in vitro anti-oxidative activity - Yu-Feng Cha; Shun Zhang; Hang Su; Yu Ou; Xiao-Zhong Fu; Feng-Jie Jiang; Yong-Long Zhao; Yong-Xi Dong; Min Luo; Yong Huang; Yan-Yu Lan; Ai-Min Wang; et al. (Medicinal Chemistry Research, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Conjugated linoleic acid alters growth performance, tissue lipid deposition, and fatty acid composition of darkbarbel catfish (Pelteobagrus vachelli) - Gui-Fang Dong; Wen-Zuo Liu; Lin-Zhou Wu; Deng-hang Yu; Feng Huang; Peng-Cheng Li; Yan-ou Yang (Fish Physiology and Biochemistry, 2015)

RETRACTED ARTICLE: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2014)

Profiling of StvacINV1 Expression in Relation to Acid Invertase Activity and Sugar Accumulation in Potato Cold-Stored Tubers - Yongbin Ou; Botao Song; Xun Liu; Yuan Lin; Huiling Zhang; Meng Li; Hui Fang; Jun Liu (Potato Research, 2013)

Transcriptional responses of maize seedling root to phosphorus starvation - Hai-Jian Lin; Jian Gao; Zhi-Ming Zhang; Ya-Ou Shen; Hai Lan; Li Liu; Kui Xiang; Maojun Zhao; Shufeng Zhou; Yong-Zhong Zhang; Shi-Bin Gao; Guang-Tang Pan (Molecular Biology Reports, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

A new isoform of thioredoxin h group in potato, SbTRXh1, regulates cold-induced sweetening of potato tubers by adjusting sucrose content - Tianjiu He; Botao Song; Jun Liu; Xia Chen; Yongbin Ou; Yuan Lin; Huiling Zhang; Conghua Xie (Plant Cell Reports, 2012)

Sequencing and analysis of the complete genome of Rana grylio virus (RGV) - Xiao-Ying Lei; Tong Ou; Ruo-Lin Zhu; Qi-Ya Zhang (Archives of Virology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

A System Dynamic Model and Sensitivity Analysis for Simulating Domestic Pollution Removal in a Free-Water Surface Constructed Wetland - Yung-Chieh Wang; Yu-Pin Lin; Chun-Wei Huang; Li-Chi Chiang; Hone-Jay Chu; Wen-Sheng Ou (Water, Air, & Soil Pollution, 2012)

Cloning and expression of the two new variants of Nav1.5/SCN5A in rat brain - Cheng-Tao Ren; Dong-Mei Li; Shao-Wu Ou; Yun-Jie Wang; Yi Lin; Zhi-Hong Zong; Masaki Kameyama; Asako Kameyama (Molecular and Cellular Biochemistry, 2012)

Characterization, and expression profile of a phenylalanine ammonia lyase gene from Jatropha curcas L. - Jihai Gao; Shuwen Zhang; Feng Cai; Xiaojiang Zheng; Na Lin; Xiaobo Qin; Yangchao Ou; Xiaoping Gu; Xihong Zhu; Ying Xu; Fang Chen (Molecular Biology Reports, 2012)

The effect of the expression of virulence-associated DEAD-box RNA helicase mRNA on the imbalance of Th1-Th2 cytokines in the CSF of patients with Cryptococcus neoformans meningitis - L. Jiang; N. Lin; Z. Cheng; B. Yang; Q. Ou (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Systematic analysis of potato acid invertase genes reveals that a cold-responsive member, StvacINV1, regulates cold-induced sweetening of tubers - Xun Liu; Chi Zhang; Yongbin Ou; Yuan Lin; Botao Song; Conghua Xie; Jun Liu; Xiu-Qing Li (Molecular Genetics and Genomics, 2011)

Characterization and expression of chicken selenoprotein W - Bor-Rung Ou; Mei-Jung Jiang; Chao-Hsiang Lin; Yu-Chuan Liang; Kuei-Jen Lee; Jan-Ying Yeh (BioMetals, 2011)

Mechanism of the Specific Neuronal Toxicity of a Type I Ribosome-Inactivating Protein, Trichosanthin - Ou Sha; David Tai-Wai Yew; Eric Yu-Pang Cho; Tzi-Bun Ng; Lin Yuan; Wing-Hang Kwong (Neurotoxicity Research, 2010)

Simulation on the dynamics of forest area changes in Northeast China - Xiangzheng Deng; Qun’ou Jiang; Jinyan Zhan; Shujin He; Yingzhi Lin (Journal of Geographical Sciences, 2010)

A New Phosphorimetry for the Determination of Trace Alkaline Phosphatase Using Multi-wall Carbon Nanotubes and Its Diagnosis of Human Diseases - Jia-Ming Liu; Ying Rao; Li Chen; Xin-Xing Wang; Li-Ping Lin; Chang-Qing Lin; Li-Hong Zhang; Ying Ou-Yang (Journal of Fluorescence, 2010)

Monoamine oxidase A gene polymorphisms and enzyme activity associated with risk of gout in Taiwan aborigines - Hung-Pin Tu; Albert Min-Shan Ko; Shu-Jung Wang; Chien-Hung Lee; Rod A. Lea; Shang-Lun Chiang; Hung-Che Chiang; Tsu-Nai Wang; Meng-Chuan Huang; Tsan-Teng Ou; Gau-Tyan Lin; Ying-Chin Ko (Human Genetics, 2010)

Transpositional activation of mPing in an asymmetric nuclear somatic cell hybrid of rice and Zizania latifolia was accompanied by massive element loss - X. H. Shan; X. F. Ou; Z. L. Liu; Y. Z. Dong; X. Y. Lin; X. W. Li; B. Liu (Theoretical and Applied Genetics, 2009)

Induction of nucleoside phosphorylase in Enterobacter aerogenes and enzymatic synthesis of adenine arabinoside - Xiao-kun Wei; Qing-bao Ding; Lu Zhang; Yong-li Guo; Lin Ou; Chang-lu Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Review of Countermeasures against Beach Erosion on the Taiwanese Coast - Tai-Wen Hsu; I-Fan Tseng; Ta-Yuan Lin; Chih-Yung Shin; Shan-Hwei Ou (Coastal Management, 2008)

Residual Stress Patterns Affect Cell Distributions on Injection-Molded Poly-l-Lactide Substrate - Sheng-Yang Lee; How Tseng; Keng-Liang Ou; Jen-Chang Yang; Kuo-Ning Ho; Che-Tong Lin; Haw-Ming Huang (Annals of Biomedical Engineering, 2008)

Static Magnetic Fields Promote Osteoblast-Like Cells Differentiation Via Increasing the Membrane Rigidity - Kang-Hsuan Chiu; Keng-Liang Ou; Sheng-Yang Lee; Che-Tong Lin; Wei-Jen Chang; Chang-Chih Chen; Haw-Ming Huang (Annals of Biomedical Engineering, 2007)

Cloning and characterization of a novel Δ12-fatty acid desaturase gene from the tree Sapium sebiferum - Bei Niu; Huaxun Ye; Ying Xu; Shenghua Wang; Peng Chen; Shuming Peng; Yangchao Ou; Lin Tang; Fang Chen (Biotechnology Letters, 2007)

Changes of Src-suppressed C kinase substrate expression in cytokine induced reactive C6 glioma cells - Lin-Lin Sun; Chun Cheng; Hai-Ou Liu; Feng Xiao; Jing Qin; Xiao-Yi Shao; Ai-Guo Shen (Neuroscience Bulletin, 2007)

Extent and pattern of DNA methylation alteration in rice lines derived from introgressive hybridization of rice and Zizania latifolia Griseb - Z. Y. Dong; Y. M. Wang; Z. J. Zhang; Y. Shen; X. Y. Lin; X. F. Ou; F. P. Han; B. Liu (Theoretical and Applied Genetics, 2006)

Distribution characteristics of SOM and nitrogen on the eastern slope of Gongga Mountain - Wang Lin; Ou Yang Hua; Peng Kui; Tian Yuqiang; Zhang Feng (Journal of Geographical Sciences, 2004)